2006
DOI: 10.1002/hup.816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative reinforcer and craving on the choice to smoke cigarettes in the laboratory

Abstract: We examined to what extent craving for cigarettes and the magnitude of an alternative monetary reinforcer were predictors of the choice to smoke in the human laboratory. Twelve non-treatment-seeking nicotine-dependent volunteers participated in a series of outpatient sessions during which they had repeated opportunities to select between three puffs of a cigarette and a variety of monetary alternatives ($0.50-3), responding under a progressive-ratio schedule. Level of cigarette craving was measured at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
5
18
0
Order By: Relevance
“…Still, the present results are consistent with demonstrations that the availability of alternative rein-forcers can decrease drug use in animals (Carroll et al 2001; Lesage 2009) and humans (Higgins et al 1994; Heishman et al 2000) and that tobacco seeking in humans can be increased by devaluation of a concurrently available food reinforcer through specific satiety (Hogarth 2012; Hogarth and Chase 2011). Interestingly, the option of receiving an alternative reinforcer (money) instead of smoking cigarettes can decrease smoking (e.g., Bisaga et al 2007), but in a meta-analysis, such options were found to have a weaker effect on tobacco use than on heroin or cocaine use (Prendergast et al 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the present results are consistent with demonstrations that the availability of alternative rein-forcers can decrease drug use in animals (Carroll et al 2001; Lesage 2009) and humans (Higgins et al 1994; Heishman et al 2000) and that tobacco seeking in humans can be increased by devaluation of a concurrently available food reinforcer through specific satiety (Hogarth 2012; Hogarth and Chase 2011). Interestingly, the option of receiving an alternative reinforcer (money) instead of smoking cigarettes can decrease smoking (e.g., Bisaga et al 2007), but in a meta-analysis, such options were found to have a weaker effect on tobacco use than on heroin or cocaine use (Prendergast et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Such choice procedures provide a more complete model of the decision processes governing human drug-seeking behavior. For example, laboratory studies of choice between drug and nondrug reinforcers in humans have shown that drug use can be reduced by increasing the magnitude of the alternative reinforcer (Higgins et al 1994; Bisaga et al 2007) and that preference for drugs over nondrug reinforcers is associated with the individual’s level of drug dependence (Hogarth 2012; Moeller et al 2009) and propensity to relapse (Moeller et al 2013; Perkins et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…The role of NMDAR in sexual behavior has been minimally examined through systemic or intra-medial preoptic area administration of MK-801, which impaired sex behavior in naïve and experienced male rats [61], [62], [63]. NMDAR also mediate other natural rewards as NMDAR antagonists decreased food intake in baboons [64] and enhanced food craving in rats [65]. NMDAR expression in the NAc is altered by cocaine exposure, and longer (3 weeks) but not short (1 day) abstinence periods from repeated cocaine increased the expression of NMDAR subunits (NR1, NR2A, NR2B) [55], [60].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In contrast to adult smokers, the extent to which adolescent smokers' behavior may be sensitive to alternative reinforcers has not been thoroughly studied in the laboratory. Studies on other aspects of adolescent smoking behavior have demonstrated that adolescent smokers are unlike adult smokers in important ways.…”
mentioning
confidence: 99%